Multimodal US–gamma imaging using collaborative robotics for cancer staging biopsies - Esposito, Marco; Busam, Benjamin; Hennersperger, Christoph; Rackerseder, Julia; Navab, Nassir; Frisch, Benjamin (International Journal of Computer Assisted Radiology and Surgery, 2016)
Purpose: The staging of female breast cancer requires detailed information about the level of cancer spread through the lymphatic system. Common practice to obtain this information for patients with early-stage cancer is sentinel lymph node (SLN) biopsy, where LNs are radioactively identified for surgical removal and subsequent histological analysis. Punch needle biopsy is a less invasive approach but suffers from the lack of combined anatomical and nuclear information. We present and evaluate a system that introduces live collaborative robotic 2D gamma imaging in addition to live 2D ultrasound to identify SLNs in the surrounding anatomy. Methods: The system consists of a robotic arm equipped with both a gamma camera and a stereoscopic tracking system that monitors the position of an ultrasound probe operated by the physician. The arm cooperatively places the gamma camera parallel to the ultrasound imaging plane to provide live multimodal visualization and guidance. We validate the system by evaluating the target registration errors between fused nuclear and US image data in a phantom consisting of two spheres, one of which is filled with radioactivity. Medical experts perform punch biopsies on agar–gelatine phantoms with complex configurations of hot and cold lesions to provide a qualitative and quantitative evaluation of the system. Results: The average point registration error for the overlay is 1.12 ± 0.57 mm. The time of the entire procedure was reduced by 36 %, with 80v of the biopsies being successful. The users’ feedback was very positive, and the system was deemed to be very intuitive, with handling similar to classic US-guided needle biopsy. Conclusion: We present and evaluate the first medical collaborative robotic imaging system. Feedback from potential users for SLN punch needle biopsy is encouraging. Ongoing work investigates the clinical feasibility with more complex and realistic phantoms.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast cancer; Inside-out tracking; Interventional imaging; Medical robotics; Multimodal imaging